Characterisation and clinical studies of an antimicrobial urinary catheter for long-term use - Belfield, Katherine (2018)
Background and Aims: Catheter-associated urinary tract infections (CAUTI) are a common and costly complication of indwelling urinary catheterisation. No commercial technology exists that protects against the major uropathogens for the lifetime of a long-term catheter. Silicone indwelling urinary catheters were impregnated with the antimicrobials (AUC) rifampicin, sparfloxacin, and triclosan to confer antimicrobial activity. With the overall aim of delivering this technology to urinary catheters users, this thesis aims to firstly, understand the profile of micoorganisms attached to indwelling urinary catheters. Secondly, using a combination of studies investigating the impregnated catheter surface and in vitro models, determine the ability of the AUC to resist mineral encrustation. Thirdly, this thesis will assess the protective activity of the AUC against multi-drug resistant organisms and Enterococcus spp. Finally, the safety and patient acceptability of this AUC will be assessed by a single-centre clinical trial.